The Hippo Pathway Is Essential for Maintenance of Apicobasal Polarity in the Growing Intestine of Caenorhabditis elegans. Issue 2 (1st October 2019) - Lee, Hanee; Kang, Junsu; Ahn, Soungyub; Lee, Junho
Abstract: Although multiple determinants for establishing polarity in membranes of epithelial cells have been identified, the mechanism for maintaining apicobasal polarity is not fully understood. Here, we show that the conserved Hippo kinase pathway plays a role in the maintenance of apicobasal polarity in the developing intestine of Caenorhabditis elegans . We screened suppressors of the mutation in wts-1 —the gene that encodes the LATS kinase homolog, deficiency of which leads to disturbance of the apicobasal polarity of the intestinal cells and to eventual death of the organism. We identified several alleles of yap-1 and egl-44 that suppress the effects of this mutation. yap-1 encodes a homolog of YAP/Yki, and egl-44 encodes a homolog of TEAD/Sd. WTS-1 bound directly to YAP-1 and inhibited its nuclear accumulation in intestinal cells. We also found that NFM-1, which is a homolog of NF2/Merlin, functioned in the same genetic pathway as WTS-1 to regulate YAP-1 to maintain cellular polarity. Transcriptome analysis identified several target candidates of the YAP-1-EGL-44 complex including TAT-2, which encodes a putative P-type ATPase. In summary, we have delineated the conserved Hippo pathway in C. elegans consisting of NFM-1-WTS-1-YAP-1-EGL-44 and proved that the proper regulation of YAP-1 by upstream NFM-1 and WTS-1 is essential for maintenance of apicobasal membrane identities of the growing intestine.